The Real Effects of Private Equity Buyouts - Joacim Tåg (Research Institute of Industrial Economics (IFN), 2010)
Private equity buyouts have become a common element in the industrial development process. I survey the literature on the real economic effect of buyouts: employment, wages, productivity, and long-run investments. Employment tend to marginally fall after a buyout in most countries studied, with the exception being France. There are clear evidence of productivity gains following a buyout, with part of these being shared with worker through higher wages. The evidence is mixed regarding effects on long-run investments.
Keywords: G20; G30; G34; J20; L20; 330; Employment; Innovation; Leveraged Buyouts; Long-run investments; Private equity buyouts; Productivity; Real effects; Private Equity; Übernahme; Kapitalstruktur; Unternehmenserfolg; Welt